Bilateral balanced occlusion compared to other occlusal schemes in complete dentures: A systematic review - Lemos, C. A.A. [UNESP]; Verri, F. R. [UNESP]; Gomes, J. M.L. [UNESP]; Santiago Júnior, J. F.; Moraes, S. L.D.; Pellizzer, E. P. [UNESP] (Wiley, 2018)
No consensus has been reached regarding the best occlusal scheme for making complete dentures. Thus, the purpose of this systematic review was to compare bilateral balanced occlusion (BBO) with other occlusal schemes (canine guidance, lingualised occlusion and zero degree) in complete dentures. The schemes were compared in terms of quality of life/satisfaction and masticatory performance. Two independent reviewers performed a comprehensive search of studies published in or before October 2017 using the PubMed/MEDLINE, Scopus and Cochrane Library databases. The search was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The focused question was: “In conventional complete denture, is BBO better than lingualised occlusion, canine guidance and zero degree in terms of quality of life, patient satisfaction and masticatory performance/muscle activity?” Seventeen studies were selected for analysis. In total, there were 492 patients with a mean age of 64.78 years and a mean follow-up duration of 2.96 months (range: 1-6 months). All studies compared BBO with the other occlusal schemes. Eleven studies evaluated the influence of the occlusal scheme designs on quality of life and satisfaction, and 8 studies evaluated masticatory performance and muscle activity between BBO and the other occlusion schemes. The present systematic review indicated that BBO does not confer better quality of life/satisfaction or masticatory performance and muscle activity. Thus, lingualised occlusion can be considered a predictable occlusal scheme for complete dentures in terms of quality of life/satisfaction and masticatory performance, while canine guidance can be used to reduce muscular activity.
Keywords: complete denture; dental occlusion; edentulous mouth; masticatory performance; patient satisfaction